POLYSEMY PROBLEM IN LEGAL TRANSLATION - NOWAK-KORCZ, Paulina (Comparative Legilinguistics, 2016)
The aim of this paper is to prove that polysemy can be a source of translation problems in legal translation. This paper deals with the analysis of errors and mistakes resulting from polysemy which have been noticed in the Polish translation of the EU regulation, namely The Council Regulation (EC) no 1346/2000 of 29 May 2000 on insolvency proceedings from French into Polish. In the first part, the article presents the definition and typology of errors and mistakes in legal translation. In the second part, the author focuses her attention on polysemy and the errors and mistakes connected with the phenomenon of polysemy. The author presents a juxtaposition of French and Polish versions of the analyzed Regulation and points out French polysemic terms found in this Regulation. The examples of translation problems resulting from polysemy have been discussed. The corrected version of the Regulation translation into Polish has also been presented.